2021
DOI: 10.21203/rs.3.rs-86672/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-dose IL-34 has no effect on osteoclastogenesis but promotes osteogenesis of hBMSCs partly via activation of the PI3K/AKT and ERK signaling pathways

Abstract: Background: Inflammatory microenvironment is significant to the differentiation and function of mesenchymal stem cells(MSCs). It evidentially influences the osteoblastogenesis of MSCs. IL-34, a newly discovered cytokine, playing a key role in metabolism. However, the research on its functional role in the osteogenesis of MSCs was rarely reported. Here, we described the regulatory effects of low-dose IL-34 on both osteoblastogenesis and osteoclastogenesis.Methods: We performed the osteogenic effects of hBMSCs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…The PI3K/Akt signaling pathway is known to be inextricably linked with various biological processes, including inflammatory response and osteogenesis process (Wu et al, 2023;Xu, Fu, et al, 2021;Zhao et al, 2022). As previously mentioned, the KEGG analysis of the microarray revealed that this pathway was enriched.…”
Section: Discussionmentioning
confidence: 68%
“…The PI3K/Akt signaling pathway is known to be inextricably linked with various biological processes, including inflammatory response and osteogenesis process (Wu et al, 2023;Xu, Fu, et al, 2021;Zhao et al, 2022). As previously mentioned, the KEGG analysis of the microarray revealed that this pathway was enriched.…”
Section: Discussionmentioning
confidence: 68%